2019
DOI: 10.1002/ygh2.337
|View full text |Cite
|
Sign up to set email alerts
|

De‐escalating medical therapy in Crohn’s disease patients who are in deep remission: A RAND appropriateness panel

Abstract: Summary Background Deep remission is a treatment goal for patients with Crohn's disease, after which de‐escalation of medical therapy may be considered. However, applicability of available study data to real‐world clinical practice can be challenging. Aim We evaluated the appropriateness of de‐escalating immunomodulator or anti‐tumour necrosis factor therapy in Crohn's disease patients in deep remission. Methods A literature review was presented to a panel of international experts in Crohn's disease. Appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…While there is consensus on initiation immunomodulatory and biologics therapies in Crohn's disease, there is considerable disagreements among clinicians in relation to withdrawal of therapies particularly in relation to its timing, monitoring of patients following withdrawal and also the longer term safety and efficacy of withdrawal strategies. Hence the RAND appropriateness panel study by Sparrow et al in the current issue of the journal is both timely and relevant to practicing clinicians.…”
mentioning
confidence: 84%
“…While there is consensus on initiation immunomodulatory and biologics therapies in Crohn's disease, there is considerable disagreements among clinicians in relation to withdrawal of therapies particularly in relation to its timing, monitoring of patients following withdrawal and also the longer term safety and efficacy of withdrawal strategies. Hence the RAND appropriateness panel study by Sparrow et al in the current issue of the journal is both timely and relevant to practicing clinicians.…”
mentioning
confidence: 84%
“…Factors that need to be accounted for when considering de-escalation of therapy include age, sex, treatments given and severity of CD. 34 A systematic review 34 anti-tumour necrosis factor (TNF) or immunomodulator (IM) therapy in people with CD who were in deep remission for at least 6 months found that de-escalating medical therapy in this cohort was appropriate for a small proportion of carefully selected people only, predominantly the elderly and those with non-severe disease.…”
Section: Management Of Crohn's Diseasementioning
confidence: 99%
“…Finally, should we de‐escalate treatment of IBD patients who are in “deep remission”? With limited studies available Sparrow et al reported on the findings of a RAND panel of international experts in Crohn's disease . This paper merits a critical commentary of its own …”
mentioning
confidence: 90%
“…This issue of GastroHep features three papers on inflammatory bowel diseases (IBD) . The first paper by Cristina Bezzio et al looks into the barriers to anti‐TNFalpha prescription among Italian physicians managing inflammatory bowel disease .…”
mentioning
confidence: 99%